Relatório de estágio curricular supervisionado em medicina veterinária - área de concentração: biotécnicas da reprodução em bovinos - (:unkn) unknown (Universidade Federal do Pampa, 2019)
This report aims to describe the main activities developed and monitored during the period of the Supervised Curricular Internship in Veterinary Medicine (ECSMV). Being carried out with a focus on Biotechnology of Applied Reproduction in Cattle, where it was possible to follow activities such as follicular aspiration guided by ultrasound, pregnancy diagnosis, in vitro embryo production, Embryo cryopreservation, embryo innovation in recipients. The place chosen for the internship was ABS Pecplan, which owns the IVB technology, from the company In Vitro Brasil S / A (IVB), in the Uberaba - MG unit. The ECSMV took place under the guidance of Professor Dr. Fernando Silveira Mesquita and supervision of Veterinary Doctor Luisa Anastácia Santos de Oliveira during the period from January 14 to April 18, 2019, totaling 536 hours. In this way, the main biotechniques applied to reproduction could be monitored and / or developed, which are directly linked to the increase in productive and reproductive indices, as well as to the increase in genetic gain generated in herds.
Report of supervised curricular internship in veterinary medicine - area of concentration: biotechniques of breeding in cattle
Keywords: Medicina veterinária; Melhoramento genético; Produção in vitro de embriões; Reprodução bovina; Reprodução animal; Genética veterinária; Genetic improvement; In vitro embryo production; Bovine reproduction; CNPQ::CIENCIAS AGRARIAS